ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN (Studi Kasus pada PT MULIA USAHA BERSAMA) - Silvi Nurfiana; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the application of existing sales information systems in manufacturing companies at PT MULIA USAHA BERSAMA in Malang Regency. This type of research uses a qualitative method with a descriptive approach. The data obtain need are based on the results of interviews with research subjects. The technique used to analyze the existing sales system at PT MULIA USAHA BERSAMA is by collecting data and then processing it so that conclusions can be drawn what kind of sales system has been implemented. The result of this study is a sales accounting information system that has many benefits for owners and for students at the Islamic University of Malang.Keywords: Sales, System, Analysis